2012
DOI: 10.1002/cncr.27677
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on metabolic factors and risk of prostate cancer

Abstract: The authors found no evidence of an association between high levels of metabolic factors and the risk of prostate cancer, but high BMI, elevated blood pressure, and a composite score of all metabolic factors were associated with an increased risk of death from prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 51 publications
(138 reference statements)
6
83
3
1
Order By: Relevance
“…Cancer Epidemiol Biomarkers Prev; 24(7) July 2015 Cancer Epidemiology, Biomarkers & Preventionand 10 cohort studies) were included in this analysis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In the 14 included studies, the retrospective cohort study by Farwell and colleagues (18) was also included because it prospectively measured serum cholesterol levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer Epidemiol Biomarkers Prev; 24(7) July 2015 Cancer Epidemiology, Biomarkers & Preventionand 10 cohort studies) were included in this analysis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In the 14 included studies, the retrospective cohort study by Farwell and colleagues (18) was also included because it prospectively measured serum cholesterol levels.…”
Section: Resultsmentioning
confidence: 99%
“…Some epidemiologic studies and preclinical models also suggest that high levels of cholesterol in blood may be associated with the risk of prostate cancer (6). However, the findings from these epidemiologic studies are inconsistent (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), as some studies have reported that high levels of cholesterol increased risk of prostate cancer (15,16,18), and some studies have reported no association between cholesterol and risk of prostate cancer (10-14, 17, 19, 21-23). Moreover, high cholesterol has been proposed to be closely associated to late-stage prostate cancer, and cholesterol may play a promotional role in late-stage prostate cancer development and progression (11,15,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In 19 studies, the source of population was the general population [16,17,18,19,23,24,25,26,27,28,29,31,33,34,35,36,37,38]; two populations were cohorts of university students [20,30] and two were professional groups [24,32]. Almost all populations were more than 90% Caucasian.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid duplicate information from overlapping studies, we removed 12 studies because their results were pooled or updated. The remaining 23 studies were included in this review [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation